The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/nano10081448
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide: Graphene Quantum Dot Nanocomposite for Better Memristic Switching Behaviors

Abstract: Tristable memristic switching provides the capability for multi-bit data storage. In this study, all-inorganic multi-bit memory devices were successfully manufactured by the attachment of graphene quantum dots (GQDs) onto graphene oxide (GO) through a solution-processable method. By means of doping GQDs as charge-trapping centers, the device indium-tin oxide (ITO)/GO:0.5 wt%GQDs/Ni revealed controllable memristic switching behaviors that were tunable from binary to ternary, and remarkably enhanced in contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Resistive switching random access memory (RRAM) can act as a synapse in a neuromorphic chip because of its low-power operation [7], fast switching time [8], high-density integration [9], and multi-level cells (MLC) with analogue switching [10][11][12][13][14]. The various resistive switching characteristics are achieved using a dielectric material and metal electrodes [15][16][17][18][19][20][21][22][23][24][25][26][27]. Additionally, the switching type can be changed depending on the operation conditions, such as the current and voltage levels [28].…”
Section: Introductionmentioning
confidence: 99%
“…Resistive switching random access memory (RRAM) can act as a synapse in a neuromorphic chip because of its low-power operation [7], fast switching time [8], high-density integration [9], and multi-level cells (MLC) with analogue switching [10][11][12][13][14]. The various resistive switching characteristics are achieved using a dielectric material and metal electrodes [15][16][17][18][19][20][21][22][23][24][25][26][27]. Additionally, the switching type can be changed depending on the operation conditions, such as the current and voltage levels [28].…”
Section: Introductionmentioning
confidence: 99%
“…Later, the GNMI/CNCCCO electrode was removed from the SC and the FTIR spectrum was measured on its surface, see Figure 7b. It shows new bands at 3100, 1625, 1070 and 945 cm −1 associated with OH‐groups, C=O, C−O−C and CO−OH, [52,53] respectively. The band at 465 cm −1 is ascribed to metal−oxygen bonds.…”
Section: Resultsmentioning
confidence: 99%
“…The researchers found that the prepared GO graphene quantum dots as the resistive layer of the device can enhance the performance, such as [185], the device could achieve ternary storage, the ON/OFF current ratio could reach a maximum of 3000, the number of endurance cycles could reach 612, and the device performance significantly increased, [186], the middle resistive layer was GOQDS:PVA, the device exhibited WORM behavior, with ON/OFF current ratio up to 3.3 × 10 4 , and a small set voltage (−0.9 V), Ag/N-GOQDs/Pt devices in [113], which can simulate neural synapses. Some researchers also doped quantum dots into GO-based memory, such as doped graphene quantum dots [106,187], and NC quantum dots [188].…”
Section: Doping With Quantum Dotsmentioning
confidence: 99%